Oral Microbiota of the Snake Bothrops lanceolatus in Martinique - Résière, Dabor (Int J Environ Res Public Health, 2018)
In Martinique, Bothrops lanceolatus snakebite, although relatively uncommon (~30 cases/year), may result in serious complications such as systemic thrombosis and local infections. Infections have been hypothesized to be related to bacteria present in the snake’s oral cavity. In this investigation, we isolated, identified, and studied the susceptibility to beta-lactams of bacteria sampled from the oral cavity of twenty-six B. lanceolatus specimens collected from various areas in Martinique. Microbiota from B. lanceolatus oral cavity was polymicrobial. Isolated bacteria belonged to fifteen different taxa; the most frequent being Aeromonas hydrophyla (present in 50% of the samples), Morganella morganii, Klebsiella pneumoniae, Bacillus spp., and Enterococcus spp. Analysis of antibiotic susceptibility revealed that 66.7% of the isolated bacteria were resistant to amoxicillin/clavulanate. In contrast, the majority of isolated bacteria were susceptible to the third-generation cephalosporins (i.e., 73.3% with cefotaxime and 80.0% with ceftazidime). Microbiota from B. lanceolatus oral cavity is polymicrobial with bacteria mostly susceptible to third-generation cephalosporins but rarely to amoxicillin/clavulanate. In conclusion, our findings clearly support that first-line antibiotic therapy in the B. lanceolatus-bitten patients, when there is evidence of infection, should include a third-generation cephalosporin rather than amoxicillin/clavulanate.